EXPRESSION OF THE GREEN FLUORESCENCE PROTEIN (GFP) IN THE CULTURED MAMMALIAN CELLS - Hà, Nguyễn Hải; Hiền, Lê Thị Thu; Hải, Nông Văn (Vietnam Journal of Biotechnology, 2011)
Cultured mammalian cells have been extensively utilized as platform for recombinant protein production because of their post-translational modifications. Several rodent- or human derived cells like CHO, HBK and HEK are frequently used for complex protein expression. Despite the plenitude of cell lines, nearly 70% of all recombinant therapeutic proteins produced today are made in CHO cells. In order to establish a protein expression system in CHO cells, the gene encoding the green fluorescence protein, GFP, was selected as the target gene of this study. pEGFP-N2 vector containing the g/^ gene -was delivered into cells by calcium phosphate or lipofectamin 2000. Forty-eight hours after transfection, the GFP expression was checked by its fluorescent intensity under a fluorescent microscopy. The fransfected cells are about 50 - 60% ofthe total cells. The stable transfected cell line named CHO/GFP expressing high level of the GFP was selected by geneticine antibiotic. These results showed the applicability of the modem cell cultured techniques for transient fransfection and stable transfected cell line development to study the expression of therapeutic recombinant proteins in the CHO cell system